Effectiveness and safety of rivaroxaban in patients with atrial fibrillation and heart failure in clinical practice: an indirect comparison of national and international registries - Cepeda, Jose Maria; Manito, Nicolas; Recio Mayoral, Alejandro; Lekuona, Iñaki; Castillo Orive, Miguel; Blanco Labrador, Elvira; Blasco, María Teresa; Farré, Nuria; García Pinilla, José Manuel; Jiménez-Candil, Javier; Rafols, Carles; Gomez Doblas, Juan Jose (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe objective of the study was to analyze and compare the effectiveness and safety of rivaroxaban in patients with atrial fibrillation (AF) and heart failure (HF).MethodsThe clinical profile and outcomes of the FARAONIC study were indirectly compared with those of the ROCKET-AF trial and other national and international observational registries.ResultsIn FARAONIC, the median age was 73.7 years, 34.1% were women, and the median CHA2DS2-VASc was 4.1. In the rivaroxaban arm of ROCKET-AF in patients with HF, these statistics were 72 years, 39.1%, and 5.1, respectively. In the national/international registries of patients with HF receiving rivaroxaban, these statistics were 74.0–75.3 years, 40.8%–41.4%, and 3.2–4.5, respectively. In the GLORIA-AF (dabigatran) and ETNA-AF (edoxaban) trials, these numbers were 69.9–75.3 years, 39.3%–41.6%, and 3.8–4.4, respectively. Among the HF populations, annualized rates of stroke or systemic embolism were 0.75% in FARAONIC (vs. 1.90% in ROCKET-AF, 0.92%–1.2% in national/international registries with rivaroxaban, 0.82% in GLORIA-AF, and 0.88% in ETNA-AF). Rates of major bleeding in FARAONIC were 1.55% (vs. 1.4%–3.86% in the national/international registries with rivaroxaban, 1.20% in GLORIA-AF, and 1.65% in ETNA-AF).ConclusionIn clinical practice, AF patients with HF, anticoagulated with rivaroxaban are old, have many comorbidities and have a high thromboembolic risk. Despite this, rates of adverse events are low.